2020
DOI: 10.6061/clinics/2020/e2245
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Total Brain Volume between Sexes in a Cognitively Unimpaired Elderly Population

Abstract: Although a large number of studies have shown brain volumetric differences between men and women, only a few investigations have analyzed brain tissue volumes in representative samples of the general elderly population. We investigated differences in gray matter (GM) volumes, white matter (WM) volumes, and intracranial volumes (ICVs) between the sexes in individuals older than 66 years using structural magnetic resonance imaging (MRI). METHODS: Using FreeSurfer version 5.3, we obtained the ICVs and GM and WM v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…However, normalized brain volumetric measurements with ICV were larger in women (Table 1). These observations are consistent with previous studies of sex-related brain volume differences [43–45] and suggest that women may have higher brain tissue density than men [46].…”
Section: Discussionsupporting
confidence: 92%
“…However, normalized brain volumetric measurements with ICV were larger in women (Table 1). These observations are consistent with previous studies of sex-related brain volume differences [43–45] and suggest that women may have higher brain tissue density than men [46].…”
Section: Discussionsupporting
confidence: 92%
“…We obtained GWAS summary statistics from the ENGIMA-CHARGE consortium through the corresponding data application. GWAS for the UK Biobank and ABCD cohorts were performed using a linear mixed model accounting for genotyping array, sex, age, sex*age, age 2 , sex*age 2 , and the first 20 genetic principal components to adjust further for the potential effects arising from sex differences 73 , fluctuations in brain volumes due to age differences among individuals 74 , and population stratification. Subcortical brain volumes GWAS were adjusted for the effects of total ICV.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study demonstrated the presence of significant differences in neuroanatomical structure volumes between men and women in a population sample of participants above 66 years of age. 27 It revealed that the adjusted gray and whiter matter volume was larger in women. Since the total brain volume is calculated as the sum of the gray and white matter volumes, this finding is consistent with our analysis that average nWBV was higher in women than in men.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with this study, it has been shown to be larger in women than in men, although uncorrected brain volume measurements, such as gray matter and white matter are smaller in women. 27 As the strength of its association with dementia is the same in both men and women, similar to MMSE, the higher average nWBV in women may be the contributor to lower All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 97%